2011
DOI: 10.1002/jsfa.4552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype and environment on the concentrations of starch and protein in, and the physicochemical properties of starch from, field pea and fababean

Abstract: Differences observed in the concentrations of starch and protein in pea and fababean were sufficient to be of practical significance to end-users, but the relatively small differences in amylose content and physicochemical properties of starch from pea and fababean were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 34 publications
5
43
0
3
Order By: Relevance
“…The protein concentrations recorded in our research fell within the range reported by other authors [7]. Notably, this quality indicator content showed increasing trends with the temperature rise; indeed, protein biosynthesis in faba bean seeds is affected by the interaction among genetic, cultural and climate factors [30] and it is quite intensive during the storage phase of seed development. The latter is characterized by a switch in cotyledon metabolism from cell division to cell expansion as well as by endopolyploidization [31] and the beginning of storage protein accumulation is linked with a sucrose signal originating from the onset of sucrose/H+ symporter activity [32].…”
Section: Resultssupporting
confidence: 88%
“…The protein concentrations recorded in our research fell within the range reported by other authors [7]. Notably, this quality indicator content showed increasing trends with the temperature rise; indeed, protein biosynthesis in faba bean seeds is affected by the interaction among genetic, cultural and climate factors [30] and it is quite intensive during the storage phase of seed development. The latter is characterized by a switch in cotyledon metabolism from cell division to cell expansion as well as by endopolyploidization [31] and the beginning of storage protein accumulation is linked with a sucrose signal originating from the onset of sucrose/H+ symporter activity [32].…”
Section: Resultssupporting
confidence: 88%
“…4. Starch gelatinization occurs between 60 and 95°C, depending on the species, sample preparation (flour or isolated starch), and methodology parameters used (Chung et al 2008;Hoover et al 2010;Hood-Niefer et al 2011), but it will only occur once the cotyledon moisture content is high enough. 5.…”
Section: Cooking Considerationsmentioning
confidence: 99%
“…Peas have a highly variable protein content, with one study of 59 different lines finding a range of 13.7-30.7% protein, with an average of 22.3% (Tzitzikas et al 2006), whereas a study of 10 genotypes determined a smaller range of 24.2-27.5% (Hood-Niefer et al 2012). The protein content and subsequent limiting amino acid vary depending on pulse class.…”
Section: Factors Influencing Protein Qualitymentioning
confidence: 99%
“…The protein content and subsequent limiting amino acid vary depending on pulse class. Peas have a highly variable protein content, with one study of 59 different lines finding a range of 13.7-30.7% protein, with an average of 22.3% (Tzitzikas et al 2006), whereas a study of 10 genotypes determined a smaller range of 24.2-27.5% (Hood-Niefer et al 2012). Pea protein is limiting in methionine, with respect to the requirements of a human diet (Sarwar and Peace 1986).…”
Section: Factors Influencing Protein Qualitymentioning
confidence: 99%